2013
DOI: 10.1053/j.semperi.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Progress in understanding the genetics of bronchopulmonary dysplasia

Abstract: Bronchopulmonary dysplasia (BPD) is the most common chronic lung disease of infants. Its treatment imposes considerable health care burden and costs in the perinatal and early childhood period and patients are usually left with life-long deficits in lung function. Evidence exists for different pathophysiologic pathways that can promote the structural changes that characterize BPD, including the impairment in alveolarization; however, there is increasing interest regarding heritable factors that may predispose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 42 publications
0
34
0
4
Order By: Relevance
“…A BPD genetikai rizikófaktorait tekintve jelentős elő-rehaladás következett be, számos jelölt gén van, amelyeknek szerepük lehet a jövő klinikai tanulmányaiban, majd pedig a betegség kezelésében [44,45]. A BPD komplexitására utal a genetika faktorok és a környezet tanulmányozását segítő biomarkercsalád összeállítása.…”
Section: A Bpd Egyéb Kockázati Faktoraiunclassified
“…A BPD genetikai rizikófaktorait tekintve jelentős elő-rehaladás következett be, számos jelölt gén van, amelyeknek szerepük lehet a jövő klinikai tanulmányaiban, majd pedig a betegség kezelésében [44,45]. A BPD komplexitására utal a genetika faktorok és a környezet tanulmányozását segítő biomarkercsalád összeállítása.…”
Section: A Bpd Egyéb Kockázati Faktoraiunclassified
“…[9][10][11][12] Mechanical ventilation, oxygen therapy, patent ductus arteriosus, neonatal infection, male gender, and genetic factors are other risk factors. 10,13,14 Moreover, placentamediated pregnancy complications were recently suggested to be associated with BPD. These include maternal disorders resulting from placental dysfunction such as gestational hypertension and preeclampsia and fetal disorders such as fetal growth restriction (FGR), which can occur without maternal hypertension.…”
mentioning
confidence: 99%
“…Twin studies have shown that even after controlling for covariates, genetic factors account for 53% of the variance in susceptibility to BPD (3). In the past, components of the innate immune system and antioxidant defenses, mechanisms of vascular and lung remodeling, and surfactant proteins have been the focus of genetic-association studies in BPD (4,5). Candidate genes for further research have been identified in these studies; however, any particular gene or gene pathway was not concluded to have a substantial contribution to the underlying etiology of BPD (5).…”
mentioning
confidence: 99%